Spatial Analysis of Dengue Hemorrhagic Fever Incidents Distribution and Dengue Virus Detection in Tanjung Priok Sub-District, DKI Jakarta - Kadek Lia Dwiyanthi; Onny Setiani; Mateus Sakundarno Adi (Postgraduate, University of Mataram, 2023)
In order to prevent the occurrence of dengue hemorraghic fever (DHF) outbreaks in Tanjung Priok District, it is necessary to confirm mosquito is infected with the Dengue Virus. In addition, spatial analysis map of the distribution of DHF incident based on population density as a basis for targeted and effective vector control. This study was conducted in January-July 2023, with the sample of respondents from the population of DHF patients. This study was a descriptive cross sectional study design. Coordinate data for DHF patients was taken from the patient's houses and then analyzed spatially using ArcGIS software. Mosquito eradication practice data was collected using direct measurement methods and interview observations and statistical analysis. Dengue virus detection in Ae. aegypti using the Real Time-PCR technique. Variables related to the incidence of DHF were the habit of hanging clothes and the using mosquito repellent (p- <0.05). In all sub-districts in Tanjung Priok, output results with different Z-scores were obtained but with the same pattern, namely clustered pattern. Transmission of DHF incident that occur within a radius of 500-1000 meters from the coordinates of each case allows it to spread to other sub-districts. No Dengue virus was found in the Ae. aegypti mosquito samples.